Breast cancer and fat grafting: efficacy, safety and complications—a systematic review. (December 2016) - De Decker, M.; De Schrijver, L.; Thiessen, F.; Tondu, T.; Van Goethem, M.; Tjalma, W.A.
Abstract: Autologous fat grafting (AFG) or lipofilling is nowadays a popular technique for breast reconstruction after breast cancer surgery. There is debate regarding the oncological safety and risks of this procedure in breast cancer patients. A systematic review of the literature published between January first 1995 and October first 2016 was conducted regarding the efficacy, safety and complications of this technique in breast cancer patients after their cancer treatment. The databases PubMed, Science Direct and Thomson Reuters Web of Science were used to search for qualified articles. Inclusion criteria were women with a personal history of breast cancer and at least one lipofilling procedure. Only studies containing a minimum of 20 patients were included in this systematic review. The search yielded a total of 23 suitable articles: 18 case series, 4 retrospective cohort studies and one prospective cohort study. The systematic review encompassed a total of 2419 patients. Medical imaging was used in the majority of the studies to assess the follow-up. Mammography was the most popular technique (65.2%), followed by ultrasound (47.8%) and MRI (30.4%). The prevalence of complications was the following: fat necrosis in 5.31%, benign lesions, like cysts or calcifications in 8.78%, infections in 0.96% and local cancer recurrence in 1.69%. AFG or lipofilling appears to be an oncological safe technique with a low morbidity in women with a history of breast cancer. In order to have a better understanding and evidence of the oncological safety a randomised controlled trial is urgently needed. We further recommend that all AFG be registered in the cancer register.